Practices of an agile developer working in the real world - Subramaniam, Venkat (Pragmatic Bookshelf, 2006)
These are the proven, effective agile practices that will make you a better developer. You'll learn pragmatic ways of approaching the development process and your personal coding techniques. You'll learn about your own attitudes, issues with working on a team, and how to best manage your learning, all in an iterative, incremental, agile style. You'll see how to apply each practice, and what benefits you can expect. Bottom line: This book will make you a better developer.
Includes bibliographical references (pages 179-184) and index. - Print version record
Keywords: Computer software -- Development; COMPUTERS; Software Development & Engineering; General; Computer software; Development; Agile Softwareentwicklung; Softwareentwicklung